Fault-tolerant spacecraft attitude control: A critical assessment. (1st April 2022) - Hasan, Muhammad Noman; Haris, Muhammad; Qin, Shiyin
Abstract: Given the few unsuccessful space missions in the past few decades, designing a fault-tolerant spacecraft's attitude control has piqued the scientific and academic community's attention. In recent years, fault-tolerant control (FTC) emerged as a prominent control strategy to ensure the reliability and safety of modern systems. This paper critically assesses various theoretical and practical design approaches to achieve the desired level of fault-tolerance for the spacecraft's attitude control. First, a run-through on the conventional FTC methodology for spacecraft's attitude control is briefly presented, highlighting the shortcomings. Then, the need for an autonomous FTC for present and future space missions is established. More critically, a detailed review of the latest developments in spacecraft's fault-tolerant attitude control is discussed from two perspectives: controller-basis design techniques and various controller performance characteristics. Finally, several key challenges and open research areas in designing a practical and reliable spacecraft's fault-tolerant attitude control and the window for future research prospects are discussed.